Influência da dinâmica hidrológica na distribuição espacial de jovens de Prochilodus lineatus (Valenciennes, 1836) (Characiformes, Prochilodontidae) na planície de inundação do alto rio Paraná. - Oliveira, Fernando Garcia de (2013)
The hydrological regime is considered the key factor driving ecological functioning of migratory fish species in the neotropical realm. In the upper Paraná River floodplain, the marginal lakes of the Ivinhema River are considered the natural nursery for the development and growth of the juveniles these species. However, based on the knowledge of the migration of small fish during the flow of the flooded lowland, known in Pantanal as "lufada", this study attempted to answer whether the juveniles Prochilodus lineatus disperse in the end of the flood from the environments of the Ivinhema to Baía and Paraná Rivers. Samplings were collected quarterly from March 2010 to March 2011 covering 36 environments (13 not connected and 16 connected lakes, 4 secondary channels and 3 rivers) of the Ivinhema, Baía and Paraná Rivers. The gill nets (20 m) of different mesh sizes were set for 24 hours, and checked at 8, 16 and 22 hs. From the fishes, it was obtained the standard length and stage of gonadal development. Were considered juvenile immature individuals with standard length ≤ 19.7 cm. The water level was characterized by monthly average and the description of the spatial distribution by number of individuals categorized by length classes with a interval of 1 cm. The factors for the analysis were: month (March-2010, June, September, December and March, 2011), subsystem (Ivinhema, Bahia and Paraná) and environment (closed lagoons, open lagoons, channels and rivers). The data were summarized by a non-metric multidimensional scaling (NMDS) and a PERMANOVA was applied to verify statistical differences with P < 0,05. The water level exceeded 3.5 m from January to April (2010) and March (2011). The proportion of juveniles between the subsystems ranged along the year from 37, 60, 60, 40 and 94% (Ivinhema); 49, 10, 10, 40 and 1% (Baía); and 14, 30, 20, 20 and 5% (Paraná). There was a reduction in the juveniles proportion in the Baía at the same time that increased in the Paraná (between March and June-2010), the inverse also occurring between September and December, coinciding with the receding waters and flood respectively. The direction of the water flow seemed to be the generator factor of these variations. The striking change in the proportion of juveniles observed between the months of March (2010 and 2011) suggests that the receding waters influenced the direction of the distribution to the Baía River while that the flood directed migration to the Ivinhema River. Regarding the variations of length classes between subsystems, the Baía was the most distinct, being the Paraná and Ivinhema statistically similar. The distinction of the functioning of hydrological dynamic (flood and receding waters) in the Paraná River proved an important information for the study of the spatial distribution of P. lineatus in the system floodplain-river of the upper Paraná River. The "lufada" was characterized in this region as the targeting of juveniles migration during the receding waters to the Baía subsystem (mostly) and also to Paraná. From this perspective, the results indicate that the Baía River acts as a route of trophic migration between subsystems.